2007
DOI: 10.1210/jc.2005-2668
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Accuracy of Urinary Free Metanephrines, Vanillyl Mandelic Acid, and Catecholamines and Plasma Catecholamines for Diagnosis of Pheochromocytoma

Abstract: Urinary free metanephrines were superior to urinary VMA, urinary catecholamines, and plasma catecholamines and can provide a valuable test for diagnosis of pheochromocytoma in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 33 publications
3
56
2
1
Order By: Relevance
“…Urinary metanephrines yielded the highest specificity and plasma metanephrines the highest sensitivity, in concordance with the conclusions of Sawka et al (9,11). In a retrospective study from Scotland, urinary free metanephrines had a sensitivity of 100% (specificity of 94%) compared with the sensitivity of 84% for urinary catecholamines, but plasma metanephrines were not evaluated in that study (12). However, to date few studies have reported results using a technology other than HPLC to assay plasma-fractionated metanephrines.…”
Section: Discussionsupporting
confidence: 82%
“…Urinary metanephrines yielded the highest specificity and plasma metanephrines the highest sensitivity, in concordance with the conclusions of Sawka et al (9,11). In a retrospective study from Scotland, urinary free metanephrines had a sensitivity of 100% (specificity of 94%) compared with the sensitivity of 84% for urinary catecholamines, but plasma metanephrines were not evaluated in that study (12). However, to date few studies have reported results using a technology other than HPLC to assay plasma-fractionated metanephrines.…”
Section: Discussionsupporting
confidence: 82%
“…Hickman et al (2009) report that in patients with pheochromocytoma, plasma free metanephrines displayed superior diagnostic sensitivity and specificity compared with other biochemical markers of catecholamine output and metabolism. Boyle et al (2007) came to a similar conclusion. Lionetto et al (2008) describe an HPLC-tandem mass spectrometric method for the simultaneous quantification of VMA, HVA and 5-HIAA in human urine.…”
Section: Review Of Literaturesupporting
confidence: 52%
“…However, the blood samples in that study were drawn in the sitting position, causing false-positive results when compared with the supine position used in the other studies (4,7). Boyle found urinary free metanephrines to be superior to urinary catecholamines and plasma catecholamines, but did not evaluate them against urinary hydrolyzed metanephrines or plasma free metanephrines (8).…”
Section: Introductionmentioning
confidence: 91%